16th-century calendar text “Nauka krótka…”: between the department of astrology and the monastic guide - Paszkiewicz, Matylda (Melusine. Old Literature and Culture, 2024)
The article discusses a chapter from an early sixteenth-century collection – “Conservatio sanitatis” (BOZ 69, fol. 93v-96r). “Nauka krótka…” is a collection of medical, care, and household instructions most likely transcribed from an informational calendar supplement. Astrological knowledge was used to create “Nauka krótka…”, subjected to a process of popularization that can be observed in the linguistic and content structure of the text. This popularization provides a contribution to considerations on the beginnings of scientific and popular scientific Polish language variants. The provenance of “Nauka krótka…” places this text in the circle of prognostic works developed at the Krakow Academy, which constitute both evidence of the development of astrological science at the turn of the 15th and 16th centuries, and a series of transformations that the results of research and observations underwent to reach the literate audience with content conveyed by scientific authorities.